The Effect of Liquid Smoke in Planting Media on the Growth of Mustard Greens - Riska Ayu Oktaviani; Hartanti, Dyah Ayu Sri; Puspaningrum, Yessita (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This research aims to evaluate the use of liquid smoke and different planting media, namely soil planting media and cocopeat planting media on the growth of mustard greens. Liquid smoke is used because it is known to contain organic compounds that can act as natural fertilizers and pesticides. This research uses a quantitative method of 2 factors, namely differences in planting media and liquid smoke treatment carried out every 3 days. The parameters measured include leaf length, leaf width and total leaves. Statistically, analysis of variance (ANOVA) shows that the differences between treatments have a significance of ≤ 0.050 (α). The results showed that the use of liquid smoke had no significant effect on leaf length, but had a significant effect on leaf width and total leaves.